A novel faecal Lachnoclostridium marker for the non-invasive diagnosis of colorectal adenoma and cancer. Issue 7 (27th November 2019) - Liang, Jessie Qiaoyi; Li, Tong; Nakatsu, Geicho; Chen, Ying-Xuan; Yau, Tung On; Chu, Eagle; Wong, Sunny; Szeto, Chun Ho; Ng, Siew C; Chan, Francis K L; Fang, Jing-Yuan; Sung, Joseph J Y; et al.
Abstract : Objective: There is a need for early detection of colorectal cancer (CRC) at precancerous-stage adenoma. Here, we identified novel faecal bacterial markers for diagnosing adenoma. Design: This study included 1012 subjects (274 CRC, 353 adenoma and 385 controls) from two independent Asian groups. Candidate markers were identified by metagenomics and validated by targeted quantitative PCR. Results: Metagenomic analysis identified ' m3 ' from a Lachnoclostridium sp., Fusobacterium nucleatum ( Fn ) and Clostridium hathewayi ( Ch ) to be significantly enriched in adenoma. Faecal m3 and Fn were significantly increased from normal to adenoma to CRC (p<0.0001, linear trend by one-way ANOVA) in group I (n=698), which was further confirmed in group II (n=313; p<0.0001). Faecal m3 may perform better than Fn in distinguishing adenoma from controls (areas under the receiver operating characteristic curve (AUROCs) m3 =0.675 vs Fn =0.620, p=0.09), while Fn performed better in diagnosing CRC (AUROCs Fn =0.862 vs m3 =0.741, p<0.0001). At 78.5% specificity, m3 and Fn showed sensitivities of 48.3% and 33.8% for adenoma, and 62.1% and 77.8% for CRC, respectively. In a subgroup tested with faecal immunochemical test (FIT; n=642), m3 performed better than FIT in detecting adenoma (sensitivities for non-advanced and advanced adenomas of 44.2% and 50.8% by m3 (specificity=79.6%) vs 0% and 16.1% by FIT (specificity=98.5%)). Combining with FIT improved sensitivity of m3 for advanced adenoma to 56.8%. The combination of m3 with Fn, Ch, Bacteroides clarus and FIT performed best for diagnosing CRC (specificity=81.2% and sensitivity=93.8%). Conclusion: This study identifies a novel bacterial marker m3 for the non-invasive diagnosis of colorectal adenoma.